Epidemiology of Clostridium difficile infections in Australia: enhanced surveillance to evaluate time trends and severity of illness in Victoria, 2010–2014. Issue 3 (July 2016) - Worth, L.J.; Spelman, T.; Bull, A.L.; Brett, J.A.; Richards, M.J.
Summary: Background: With epidemic strains of Clostridium difficile posing a substantial healthcare burden internationally, there is a need for longitudinal evaluation of Clostridium difficile infection (CDI) events in Australia. Aim: To evaluate time trends and severity of illness for CDI events in Australian healthcare facilities. Methods: All CDI events in patients admitted to Victorian public hospitals between 1 st October 2010 and 31 st December 2014 were reported to the Victorian Healthcare Associated Infection Surveillance System. CDI was defined as the isolation of a toxin-producing C. difficile organism in a diarrhoeal specimen, and classified as community-associated (CA-CDI) or healthcare-associated (HA-CDI). Severe disease was defined as admission to an intensive care unit, requirement for surgery and/or death due to infection. Time trends were examined using a mixed-effects Poisson regression model, and the Walter and Edward test of seasonality was applied to evaluate potential cyclical patterns. Findings: In total, 6736 CDI events were reported across 89 healthcare facilities. Of these, 4826 (71.6%) were HA-CDI, corresponding to a rate of 2.49/10, 000 occupied bed days (OBDs). The incidence of HA-CDI was highest in the fifth quarter of surveillance (3.6/10, 000 OBDs), followed by a reduction. Severe disease was reported in 1.66% of events, with the proportion being significantly higher for CA-CDI compared with HA-CDI (2.21 vs 1.45%, P = 0.03). The highest and lowest incidence of HA-CDI occurred in March and October, respectively. Conclusions: A low incidence of HA-CDI was reported in Victoria compared with US/European surveillance reports. Seasonality was evident, together with diminishing HA-CDI rates in 2012–2014. Severe infections were more common in CA-CDI, supporting future enhanced surveillance in community settings.